Effects on labour and GDP of the CAP 2013 reform though investment in agricultural machinery: Spanish case - Cosculluela-Martínez, Carolina (Revista de Evaluación de Programas y Políticas Públicas, 2013)
This paper studies the effect of the investment in agricultural machinery on the Spanish net employment and GDP growth. Those dynamic responses to a permanent unitary shock in agricultural machinery capital stock are studied estimating a reduced form of a Structural Equation Model (SEM) where effects on all variables are considered. Results suggest that CAP 2013 negotiation in Brussels is crucial for the Spanish 25% unemployment rate. The investment of 4,5 thousand Euro increases net employment in one employee after 4 years, while other machinery requires 24,7 thousand Euro and metal machinery 47,2 thousand Euro for the same achievement. Resumen Se estudian los efectos que produce sobre el empleo neto y el PIB la inversion en maquinaria para la agricultura, ganadería y pesca. Se estudian las respuestas dinámicas a un shock unitario permanente en el stock de capital de maquinaria para la agricultura, ganadería y pesca mediante la estimación de la forma reducida de un modelo de ecuaciones estructurales, donde se permiten los efectos entre todas las variables. Los resultados sugieren que la negociación de la PAC en 2013 es crucial en el desempleo de España. La inversion de 4,500 euros genera unos efectos remanentes al cabo de cuatro años de incremento del empleo neto en un empleado, mientras que si la inversion se realiza en cualquier otra maquinaria se precisan 5,5 veces ese capital y 10,5 veces ese capital si la inversion se realiza en maquinaria metálica.